Проблеми реалізації переважного права акціонера ЗАТ та приватного АТ на придбання акцій, що відчужуються іншими акціонерами - Шевченко, Г.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируются теоретические подходы к решению проблем, связанных с реализацией преимущественного права акционеров закрытых акционерных обществ и частных акционерных обществ на приобретение акций таких обществ, которые отчуждаются другими акционерами. Раскрываются законодательные неточности и пути устранения противоречий, порожденных принятием Закона Украины ("Об акционерных обществах") в рамках выше определенных заданий. Our scientific research is dedicated to analysis of existing and forming of a new theoretical approaches to the problem solution, connected with realization of overwhelming right for the shareholders of the closed joint-stock companies and private joint-stock companies onacquisition of shares such companies, which are alienated by other shareholders. Moreover,the purpose of this research is an analysis of obvious legislative discrepancies and removal of contradictions, descendanted by adoption the Law of Ukraine «About joint-stock companies».